Sleep “ON”, sleep better! Positive effects of levodopa on sleep behaviour in people with Parkinson's disease - Costa, Elisa de Carvalho [UNESP] (2024)
People with Parkinson's disease experience reduced sleep quality compared with their peers. Levodopa may have a direct effect on sleep macrostructure or may improve sleep by enhancing nocturnal motor performance. Therefore, it is important to understand the acute effects of withdrawing levodopa on sleep measures in Parkinson's disease. The purpose of this study was to compare the estimated objective and subjective sleep measures of people with Parkinson's disease sleeping under (ON-night) versus without (OFF-night) the effects of the last daily dopaminergic medication before going to bed. A total of 23 people with Parkinson's disease were instructed to wear an actigraphy device for 4 consecutive nights to objectively measure the sleep behaviour. Subjective sleep measure was assessed each morning using a Likert scale. Participants slept for 3 nights on ON-night and 1 night on OFF-night. They were instructed not to take their last dose of levodopa before going to bed in OFF-night. Sleeping in ON- versus OFF-night increased total sleep time (7.8%, p = 0.032) and sleep efficiency (3.7%, p = 0.019), and decreased duration and number of wakes after sleep onset (22.3%, p = 0.050; and 29.2%, p = 0.013, respectively). However, subjective sleep analysis indicated no significant differences between the two conditions. From a clinical point of view, our results suggest that sleeping on ON-night resulted in an improvement in estimated objective sleep measures compared with sleeping on OFF-night. From a methodological point of view, our findings emphasize the importance of relying on objective sleep measurements to accurately assess OFF-night sleep behaviour in people with Parkinson's disease.